Gravimetría aérea para la determinación del geoide local (ING) - Serpas, Juan Gilberto (2004)
This article describes local geoid estimation using the vertical component of the gravity disturbance vector from airborne gravimetry. Even when the horizontal components of gravity disturbance vector can be used, in this study only results from the vertical component are discussed. In order to asses the quality of the geoid, results from an airborne flight in an area on the Canadian Rocky Mountains are provided. Geoid estimations by the vertical component using Hotine´s integral show accuracies of the order of 3 to 7 cm when compared to the Canadian geoid (CGG2000).